A japán jūdō terminológia magyar fordításának problémái: Támpontok egy szakzsargon megreformálásához - Gottner, Richárd Gábor (Távol-keleti Tanulmányok, 2020)
Kōdōkan jūdō is the first Japanese martial art ever introduced in Hungary, at the beginning of the twentieth century. In order to make jūdō popular among the general public, it was necessary to translate the cryptic Japanese names of the techniques to more familiar Hungarian terms, thus Hungarian jūdōterminology was born. Since then, nearly a century has passed, and partly because of the terminology, (which had no linguistic foundations but was created on the basis of mere observation by Hungarian practitioners), jūdō has drifted away from its authentic Japanese roots. In this study, I introduce the main translational errors affecting the terminology and try to offer some solutions favouring a more accurate Hungarian jūdō-terminology for the future.